Core–Shell Carbon‐Based Bifunctional Electrocatalysts Derived from COF@MOF Hybrid for Advanced Rechargeable Zn–Air Batteries. Issue 31 (9th July 2022) - Li, Wei; Wang, Jingyun; Chen, Junxiang; Chen, Kai; Wen, Zhenhai; Huang, Aisheng
Abstract: The development of highly active carbon‐based bifunctional electrocatalysts for both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is highly desired, but still full of challenges in rechargeable Zn–air batteries. Metal organic frameworks (MOFs) and covalent organic frameworks (COFs) have gained great attention for various applications due to their attractive features of structural tunability, high surface area and high porosity. Herein, a core–shell structured carbon‐based hybrid electrocatalyst (H‐NSC@Co/NSC), which contains high density active sites of MOF‐derived shell (Co/NSC) and COF‐derived hollow core (H‐NSC), is successfully fabricated by direct pyrolysis of covalently‐connected COF@ZIF‐67 hybrid. The core–shell H‐NSC@Co/NSC hybrid manifests excellent catalytic properties toward both OER and ORR with a small potential gap (∆ E  = 0.75 V). The H‐NSC@Co/NSC assembled Zn–air battery exhibits a high power‐density of 204.3 mW cm −2 and stable rechargeability, outperforming that of Pt/C+RuO2 assembled Zn–air battery. Density functional theory calculations reveal that the electronic structure of the carbon frameworks on the Co/NSC shell can be effectively modulated by the embedded Co nanoparticles (NPs), facilitating the adsorption of oxygen intermediates and leading to enhanced catalytic activity. This work will provide a strategy to design highly‐efficient electrocatalysts for application in energy conversion and storage. Abstract : Based on a "metal organic framework (MOF) and covalent organic framework (COF)" strategy and following pyrolysis process, a well‐defined hollow core–shell H‐NSC@Co/NSC electrocatalyst is developed for the fabrication of advanced rechargeable Zn–air batteries. The H‐NSC@Co/NSC–based Zn–air battery displays a high power‐density (up to 204.3 mW cm −2 ), a small charge‐discharge voltage gap and an excellent cycling stability.